Space Weather Ballooning. Issue 10 (22nd October 2016) - Phillips, Tony; Johnson, Sam; Koske‐Phillips, Amelia; White, Michael; Yarborough, Amelia; Lamb, Aaron; Herbst, Anna; Molina, Ferris; Gilpin, Justin; Grah, Olivia; Perez, Ginger; Reid, Carson; et al.
Abstract: We have developed a "Space Weather Buoy" for measuring upper atmospheric radiation from cosmic rays and solar storms. The Buoy, which is carried to the stratosphere by helium balloons, is relatively inexpensive and uses off‐the‐shelf technology accessible to small colleges and high schools. Using this device, we have measured two Forbush Decreases and a small surge in atmospheric radiation during the St. Patrick's Day geomagnetic storm of March 2015.